2015
DOI: 10.1016/j.clinthera.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Innovation in Alzheimer’s Disease Drug Development: A Strategic Assessment Based on Technological Maturity

Abstract: This analysis suggests that AD drug discovery has followed a predictable pattern of innovation in which technological maturity is an important determinant of success in development. Quantitative analysis indicates that the lag in emergence of new products, and the much-heralded clinical failures of recent years, should be viewed in the context of the ongoing maturation of AD-related technologies. Although these technologies were not sufficiently mature to generate successful products a decade ago, they may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Those technologies that did not exhibit an S-curve in this analysis exhibited an exponential growth pattern characteristic of nascent technologies, and none have generated approved NMEs. The characteristic patterns of technology growth and NME approvals observed in this study are similar to those we have observed in other studies including studies of drugs for Alzheimer’s disease and gene therapies[45, 49, 63], of which 80–90% of which exhibit the exponentiated logistic growth pattern that can be modeled with the TIME model.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Those technologies that did not exhibit an S-curve in this analysis exhibited an exponential growth pattern characteristic of nascent technologies, and none have generated approved NMEs. The characteristic patterns of technology growth and NME approvals observed in this study are similar to those we have observed in other studies including studies of drugs for Alzheimer’s disease and gene therapies[45, 49, 63], of which 80–90% of which exhibit the exponentiated logistic growth pattern that can be modeled with the TIME model.…”
Section: Discussionsupporting
confidence: 86%
“…The information value of any single publication may vary in magnitude ranging from large advances that contribute positively to knowledge, to incremental, inconsequential, or even incorrect (negative) contributions. However, when integrated over very large numbers of publications, the cumulative number of publications provides a quantifiable metric for the accumulation of knowledge[45, 63]. …”
Section: Methodsmentioning
confidence: 99%
“…Most technological developments follow and S-shaped growth curve, that can be divided into four phases: pre-development, take-off, acceleration, and stabilization [64][65][66]. Therefore, the study cases uses a sigmoid function g(t, x) to adjust the power network growth data [67]:…”
Section: Methodsmentioning
confidence: 99%
“…The second type of factors is about technology fields [3,[61][62][63]. Technology innovations, updates and applications were the central support for the progress of industrialization.…”
Section: Challenges In Industrializationmentioning
confidence: 99%